Current symptom-based risk scores for stable coronary artery disease evaluation are not applicable in COPD patients. Issue 4 (19th October 2020) - Beyer, Christoph; Pizzini, Alex; Boehm, Anna; Loeffler-Ragg, Judith; Weiss, Guenter; Feuchtner, Gudrun; Bauer, Axel; Friedrich, Guy; Plank, Fabian
Background: Cardiovascular diseases are arguably the most important comorbidity in patients with COPD. Despite an increased prevalence of coronary artery disease (CAD) in COPD patients, there are no dedicated diagnostic recommendations. Objectives: We investigated whether COPD patients receive adequate primary evaluation of CAD despite overlapping symptoms. Methods: In total, 302 patients with COPD who underwent invasive coronary angiography (ICA) were retrospectively matched (for age, body mass index and cardiovascular risk factors) with 302 patients without functional lung diseases. Quality and onset of symptoms prior to ICA were documented, and individual patients' pretest probabilities according to European Society of Cardiology (ESC) guidelines were calculated. Endpoints were delay of ICA referral after symptom onset and clinical outcome, defined as subsequent revascularisation. Results: Mean delay between symptom onset and ICA was 19.9±22.0 months in COPD patients compared to 8.3±12.7 months in the control group (p<0.0001). COPD patients had a lower rate of typical chest pain (25.2% versus 38.1%, p=0.0009), and dyspnoea only (18.2% versus 26.8%, p=0.015). Sub-analysis of Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades revealed an incremental delay with increasing COPD severity: GOLD 1: 16.1±17.3 months; GOLD 2: 17.6±22.1 months; GOLD 3: 20.1±21.3 months; and GOLD 4: 24.2±23.4 months. Overall significant CAD prevalence (>70% stenosis) was 35.3%; the revascularisation rate increased with higher pretest probability for the control group but decreased for patients with COPD GOLD 1–4. Conclusion: Patients with COPD are insufficiently evaluated for CAD due to overlapping symptoms. Current CAD risk scores for stable chest pain appear inappropriate for patients with COPD. Coronary artery disease evaluation is delayed in COPD patients compared to patients without obstructive lung disease. Due to overlapping symptoms, pretest probabilities of current stable angina models do not fit patients with COPD. https://bit.ly/318RkNz